Short-term survival of Gasterosteus aculeatus F1 offspring during the 90 day growth experiment depending on parent and offspring (beaker) heatwave treatment - Helen Spence-Jones; Lisa N S Shama (PANGAEA, 2025)
Short-term survival of F1 offspring during the 90 day growth experiment depending on parent and offspring (beaker) heatwave treatment
In: Spence-Jones, H; Shama, LNS (2025): Stickleback (Gasterosteus aculeatus) marine heatwave experiment: F0 adult size and fecundity traits, F1 offspring growth, behavior and survival, and F2 offspring egg size, clutch size, and hatchling length [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973487